INTEGRATING SOCIO-CONSTRUCTIVISM AND DIGITAL LITERACY IN SPEAKING INSTRUCTION: LESSONS FROM NORTH SUMATERA - Muhammad Hassan; Edi Suprayetno (English Study Program University of Pasir Pengaraian, 2026)
This study examines the integration of socio-constructivist principles and digital literacy in English speaking instruction within higher education in North Sumatera, Indonesia. Despite growing emphasis on communicative competence, students continue to face challenges in oral proficiency, confidence, and access to authentic interaction, highlighting a gap in the effective integration of pedagogy and technology. This research aims to design, implement, and evaluate digitally supported instructional practices that enhance speaking competence through collaborative learning environments. A convergent mixed-methods design was employed, involving 120 English education students and 12 lecturers from three universities. Data were collected through questionnaires, classroom observations, speaking performance assessments, and semi-structured interviews, and analyzed using complementary statistical and thematic techniques. The findings indicate that digital storytelling, podcast-based tasks, and collaborative multimedia projects substantially improve learners’ fluency, motivation, and self-efficacy. These outcomes reflect core socio-constructivist principles, particularly interaction, scaffolding, and learner autonomy. While lecturers demonstrated increasing digital pedagogical competence, challenges related to infrastructure and professional training remain evident. This study concludes that the integration of socio-constructivist approaches within digitally enriched learning environments promotes more communicative, multimodal, and culturally responsive speaking instruction. The proposed framework offers a sustainable model for advancing technology-integrated English language teaching in similar higher education contexts.